Iron deficiency is uncommon among lactating women in urban Nepal, despite a high risk of inadequate dietary iron intake. Issue 1 (14th July 2014) - Henjum, Sigrun; Manger, Mari; Skeie, Eli; Ulak, Manjeswori; Thorne-Lyman, Andrew L.; Chandyo, Ram; Shrestha, Prakash S.; Locks, Lindsey; Ulvik, Rune J.; Fawzi, Wafaie W.; Strand, Tor A.
<x content-type="archive" xml:space="preserve">Abstract</x> The main objective of the present study was to examine the association between dietary Fe intake and dietary predictors of Fe status and Hb concentration among lactating women in Bhaktapur, Nepal. We included 500 randomly selected lactating women in a cross-sectional survey. Dietary information was obtained through three interactive 24 h recall interviews including personal recipes. Concentrations of Hb and plasma ferritin and soluble transferrin receptors were measured. The daily median Fe intake from food was 17·5 mg, and 70 % of the women were found to be at the risk of inadequate dietary Fe intake. Approximately 90 % of the women had taken Fe supplements in pregnancy. The prevalence of anaemia was 20 % (Hb levels < 123 g/l) and that of Fe deficiency was 5 % (plasma ferritin levels < 15 μg/l). In multiple regression analyses, there was a weak positive association between dietary Fe intake and body Fe (β 0·03, 95 % CI 0·014, 0·045). Among the women with children aged < 6 months, but not those with older infants, intake of Fe supplements in pregnancy for at least 6 months was positively associated with body Fe (P for interaction < 0·01). Due to a relatively high dietary intake of non-haem Fe combined with low bioavailability, a high proportion of the women in the present study were at the risk of inadequate intake of Fe. The low prevalence of anaemia and Fe deficiency may be explained by the majority of the women consuming Fe supplements in pregnancy.